The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0240070
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and nitrite exposure leads to mild anxiogenic-like behavior and alters brain metabolomic profile in zebrafish

Abstract: Dietary nitrate lowers blood pressure and improves athletic performance in humans, yet data supporting observations that it may increase cerebral blood flow and improve cognitive performance are mixed. We tested the hypothesis that nitrate and nitrite treatment would improve indicators of learning and cognitive performance in a zebrafish (Danio rerio) model. We utilized targeted and untargeted liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis to examine the extent to which treatment resulted i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…The authors used a combination of 1 H-NMR for the analysis of monosaccharides, amino acids, and organic acids, GC-MS for cholesterol and fatty acids, and LC-MS for the analysis of lipids. However, more recent zebrafish toxicometabolomics studies (≥2017) reported using LC-HRMS (Orbitrap or QTOF) [15,28,29,31,33,36,48,51,[85][86][87][88], followed by 1 H-NMR [24,30,[89][90][91][92][93] and GC-HRMS [21,94], while multi-analytical platform studies remain scarce.…”
Section: Instrumental Analysismentioning
confidence: 99%
“…The authors used a combination of 1 H-NMR for the analysis of monosaccharides, amino acids, and organic acids, GC-MS for cholesterol and fatty acids, and LC-MS for the analysis of lipids. However, more recent zebrafish toxicometabolomics studies (≥2017) reported using LC-HRMS (Orbitrap or QTOF) [15,28,29,31,33,36,48,51,[85][86][87][88], followed by 1 H-NMR [24,30,[89][90][91][92][93] and GC-HRMS [21,94], while multi-analytical platform studies remain scarce.…”
Section: Instrumental Analysismentioning
confidence: 99%
“…Raw data was loaded to PeakView™ with XIC Manager 1.2.0 (ABSciex, Framingham, MA) for peak-picking, retention time correction, and peak alignment. Metabolite identities were confirmed as previously described by matching with an in-house library comprising IROA standards (IROA Technology, Bolton, MA) and other commercially available standards (650 total) ( García-Jaramillo et al, 2020 ). The list of identified peaks was exported to MultiQuant 3.0.2, and chromatograms integrated to obtain peak area values for all the assigned metabolites.…”
Section: Methodsmentioning
confidence: 99%
“…43 Accumulation of waste products and other metabolites, such as secreted cortisol, 32 can be problematic in both stationary and recirculating aquaculture systems affecting both development and growth of zebrafish 43,44 and adult zebrafish behavior. 45 The problem is mainly during the start-up period of the aquaria since it takes time to establish an appropriate bacterial culture of nitrifying bacteria. Although few systematic studies have been performed to investigate how water quality is affected by fish density, Pavlidis et al 32 showed a reduction in water quality and dissolved oxygen in their static tanks during the crowding experiment at 40 fish/L.…”
Section: Water Quality and Pathogensmentioning
confidence: 99%